THE EFFECT OF PREVENTIVE MAINTENANCE, TRAFFIC MANAGEMENT, TECHNOLOGY AND COMMUNICATION SUPPORT AND OPERATOR CARE ON OSH PERFORMANCE TRANSPORTATION OF TRUCK UNITS IN THE MINING SERVICE COMPANY PT. XYZ - Restu Harywibowo; Agustinus Hariadi (ABNUS Publisher, 2022)
This study aims: To determine the direction and strength of the effect of preventive maintenance on the performance of K3 transportation at Mining Service Company PT. To determine the direction and strength of the influence of traffic management on the performance of K3 transportation at the PT. To determine the direction and strength of the influence of technology and communication on the performance of K3 transportation at the PT XYZ Mining Service Company. This research is descriptive quantitative. The population in this study were 2145 workers and staff working in the construction service company PT. The sampling technique in this study is the saturated sampling technique, the samples taken are 145 workers and staff who work in the construction service company PT. The results of this study indicate that: There is an effect of preventive maintenance on the performance of K3 transportation. There is an effect of traffic management on the performance of K3 transportation. There is an effect of technology and communication support on the performance of K3 transportation. There is an effect of operator concern on the performance of K3 transportation